Regional conductance map of Andaman and Nicobar region - Subbarao, P.B.V. (My University, 2008)
To image the electrical conductivity distribution, fluxgate magnetometers are operated at five sites in Andaman and Nicobar region. Transfer functions are estimated for the period range 8–128 min, from nighttime transient geomagnetic variations, using robust regression analysis. The observed induction arrows in Andaman Islands are found to point towards east despite deep sea located towards its west. This indicates that fore-arc basin (Andaman–Nicobar deep) is more conducting than the region of outer non-volcanic Island arc. Thin sheet model requires the conductance of 10,000–35,000 S (with increase conductivity towards the south) for explaining the observed induction pattern. The observed induction pattern at Andaman–Nicobar stations can be explained in terms of high conducting Cretaceous–Tertiary sediments filling the Andaman–Nicobar deep. High conductivity over Invisible bank has been attributed to the partial melts/volatile fluids derived from the subducting Indian plate that are intruding into the eastern margin of fore-arc basin through the West Andaman Fault (WAF). The induction pattern at Great Nicobar station (Campbell Bay) may be related to the highly conducting sediments filling the Mergui basin along with mafic intrusions. Also crustal transition occurs below the Mergui Terrace at the Malayan coast contributing to the enhanced conductivity anomaly.
Keywords: Andaman–Nicobar Islands; Geomagnetic depth sounding; High conductivity; Fore-arc basin; Invisible bank; Mergui basin